Bioaffinity limitations for anisotropically etched silicon microfluidics. (26th April 2010) - Alazzam, Anas; Chandrasekaran, Arvind; Packirisamy, Muthukumaran; Stiharu, Ion; , Rama Bhat
Immobilisation of biological specimens is an essential process in biomicrofluidics for micro total analysis systems (μTASs) applications, to carry out high throughput bioassays. Closed microfluidic channels restrict immobilisation feasibilities to only direct conjugation of the biomolecules with the channel surface through appropriate flow control-based incubation techniques. In this work, the limitations of bioaffinity on anisotropically etched silicon microfluidic channels have been studied. The flow behaviour within the microchannels has been analysed by solving the Navier-Stokes equation using finite element method (FEM). The results have been used to predict the immobilisation and rinsing behaviour within anisotropically etched trapezoidal and triangular microfluidic channels.